ANALISYS OF SHARIA PRINCIPLE ADHERENCE WITH BALANCE SCORECARD METHOD IN WANOJA HIJAB SHARIA BUSINESS - Irma Kurniasih; Juliana Juliana; Hilda Manoarfa; Ropi Marlina (STIESA Press, 2021)
This research is based on the phenomenon of sharia business development in Indonesia which is still not in accordance with sharia principles, whereas on the one hand Indonesia is a country whose population is Muslim. The purpose of this study is to describe the general work of shariah run by Wanoja Hijab and analyze the relationship of Sharia Compliance Principles implementation in sharia business Wanoja Hijab calculated using Balanced Scorecard (BSC) method. The method used in this research is descriptive quantitative. Data collection using questionnaires, interviews and documentation, while data analysis techniques using Balance Scorecard analyzed in Key Perfomance Index. The company that is the subject of this research is Wanoja Hijab located in Bandung City. The number of samples in this study are 42 respondents consisting of 1 company's pipeline, 7 employees and 34 customers of Wanoja Hijab. The results show that the Hijab business is a business based on syirkah or a kind of limited liability company in sharia version. All products purchased are hijab, which is clothing for adult muslimah. Wanoja Hijab serves to promote sharia principles in the overall business process, including in employing its employees. The calculation result shows that the achievement of Sharia Compliance Principle (SPA) in sharia business Wanoja Hijab calculated using Balanced Scorecard (BSC) method reached 94.35%. The highest growth rate is achieved by the Internal Proccess dimension with a percentage of 100%, while the percentage rate owned by the learning and development dimension of employees with a percentage of only 88.2%.